Effect of External Pressure and Quantum State on the Local Magnetization of Germanium Layers: Ab Initio Calculation. Issue 3 (22nd January 2023) - Goncharov, Aleksei Vasilievich; Nikolaevich, Chibisov Andrey
Abstract: Designing stable quantum computers with the ability to correct errors responsibly requires a detailed understanding of the physical processes that underlie these devices. In this study, detailed quantum mechanical simulations of the atomic structure, charge distribution of electron density, and distribution and orientation of magnetic and quantum states as a function of applied external pressure performed for ultrathin layers of germanium. The results show that, even in the absence of holes, in the negative pressure range, the total spin is characterized by the quantum state |1〉 in the Bloch sphere. It found that the hole states predominantly localized in the volume structure of ultrathin germanium layers. In this structure, there is an ordering of magnetic states with a repetition period of 2a along the elongation axis of the slab. Abstract : Detailed quantum mechanical simulation of the atomic structure, charge distribution of electron density, and distribution and orientation of magnetic and quantum states as a function of applied external pressure are performed for ultrathin germanium layers. The localization of hole states in the bulk structure of germanium ultrathin layers and the logical quantum state of an ultrathin germanium film are established.